The Influence of Live Streaming Shopping and the FYP Algorithm on Impulsive Buying Behavior among TikTok Users of FEBI UINSU Students: Islamic Financial Literacy as a Moderating Variable - Ikhwanul Khair; Marliyah; Nur Ahmadi Bi Rahmani (Universitas Negeri Padang, 2026)
This study is motivated by the increasing trend of impulsive buying behavior among university students, driven by the development of TikTok features such as live streaming shopping and the FYP algorithm, which encourage spontaneous consumption. The aim of this study is to analyze the effect of live streaming shopping and the FYP algorithm on impulsive buying and to examine the role of Islamic financial literacy as a moderating variable among FEBI UIN North Sumatra students. This research uses a quantitative approach with an associative method through questionnaires distributed to 103 respondents and analyzed using PLS-SEM. The results show that live streaming shopping and the FYP algorithm have a positive and significant effect on impulsive buying, while Islamic financial literacy has a negative and significant effect. However, Islamic financial literacy does not act as a moderating variable. In conclusion, although students possess Islamic financial literacy, the influence of TikTok features remains strong in driving impulsive purchasing behavior.